A synthesis of changes in women's empowerment from Cultivate Africa's Future agricultural development projects - Malapit, Hazel J.; Galiè, Alessandra; Njiru, Nelly; Ferguson, Nathaniel; Omondi, Immaculate A.; Lecoutere, Els; Muchiri, Caroline (CGIAR GENDER Impact Platform, 2025)
There are few examples of assessments of project portfolios that aim to support women’s empowerment in agriculture and livestock in low- and middle-income countries and that employ a consistent framework and standardized, validated measures of women’s empowerment across the entirety of the projects (see also Baltenweck et al. 2024). This brief synthesizes and presents lessons about women’s empowerment from the achievements of a portfolio of agricultural development projects, where empowerment was consistently measured across the portfolio using the project-level Women’s Empowerment in Agriculture Index (pro-WEAI).